PENYIDIKAN TINDAK PIDANA PENYALAHGUNAAN PENYALURAN PUPUK BERSUBSIDI BERDASARKAN PERATURAN MENTERI PERDAGANGAN REPUBLIK INDONESIA NOMOR 15/M-DAG/PER/4/2013 TENTANG PENGADAAN DAN PENYALURAN PUPUK BERSUBSIDI UNTUK SEKTOR PERTANIAN DI KEPOLISIAN DAERAH RIAU - Pera Erawina Siregar; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The government has regulated regulations on subsidized fertilizers but there are still many criminal acts of misuse of subsidized fertilizer distribution. Fertilizers that are subsidized by the government are designated for farmer groups or poor farmers to help improve the economics of farmers' groups or farmers. However, in practice, fertilizers that have been subsidized by the government are misused by the perpetrators of criminal acts for their personal or group interests that result in losses to the government and loss to farmers groups or needy farmers. Abuse of subsidized fertilizers is included in economic crime. Economic crime is the act of a person who violates government regulations in economic field. The purpose of writing this thesis is first To know the role of Investigators in tackling the crime Abuse of Distribution of Subsidized Fertilizer based on Regulation of Minister of Trade of Republic of Indonesia Number 15 / M-Dag / Per / 4/2013 About Procurement and Distribution of Subsidized Fertilizer for Agricultural Sector in Riau Regional Police. Secondly to know the factors that cause the rampant Misuse of Subsidized Fertilizer Distribution.This type of research can be categorized in the type of sociological research. The research location is Riau Regional Police. Sources of data used are primary data and secondary data. Data collection techniques are questionnaires, interviews, literature review. After the data collected then analyzed qualitatively by using the deductive method of drawing the conclusions of the things that are general to things that are special.From the results of research there are two main things that can be concluded. First Role of Police Investigator in tackling crime of abuse of distribution of subsidized fertilizer for Agricultural Sector in Riau Regional Police, that in its implementation the role of police investigator is not running properly for that in this case should police investigator do preventive and repressive effort. Both factors causing widespread misuse of the distribution of subsidized fertilizers include internal and external factors.Keywords: Subsidized Fertilizer - Investigation - Crime